Trimesic acid-Ni based metal organic framework derivative as an effective destabilizer to improve hydrogen storage properties of MgH2. (10th August 2021) - Yang, Jisheng; Zhang, Kemin; Ma, Zhewen; Zhang, Xu; Huang, Tianping; Panda, Subrata; Zou, Jianxin
Abstract: Herein, a new type of trimesic acid-Ni based metal organic framework (TMA-Ni MOF) was synthesized and then, its derivative Ni@C was introduced into MgH2 as destabilizer through high energy ball milling to prepare a Mg–Ni@C–H composite. X-ray diffraction analyses indicate the formation of Mg2 Ni/Mg2 NiH4 as major phases after dehydrogenation/rehydrogenation of the composite, respectively. Two hydrogen absorption plateaus are observed in the Mg–Ni@C–H composite, corresponding to the hydrogenation of Mg and Mg2 Ni, with the enthalpy change values of −75.8 and −52.3 kJ mol −1 H2 respectively. Thus, it can be concluded that a destabilization effect is brought by Ni@C on thermodynamic properties of MgH2 . In addition, the hydriding/dehydriding kinetics of MgH2 is notably accelerated with the addition of Ni-based MOF derivative. The activation energy values of both hydrogen absorption and desorption are significantly lowered down with the assistance of Ni@C. Moreover, stable hydrogen de/absorption capacity and kinetics are remained during 25 cycles of high-rate re/dehydrogenation, which can be ascribed to the carbon-wrapped structure of the composite, with which the aggregation of the nanosized particles can be evidently avioded. Highlights: A new type of TMA-Ni-MOF nano-structured derivate was synthesized and introduced into MgH2 . The introduction of Ni@C as the destabilizer can alter the thermodynamics of the system. The "hydrogen pump" effect of Mg2 Ni/Mg2 NiH4 can accelerate hydrogen uptake/release kinetics. The carbon wrapped structure contributes to the stable cycling kinetics and capacity.